HUBUNGAN ANTARA KOMPETENSI PEDAGOGIK DAN KOMPETENSI SOSIAL GURU DI LINGKUNGAN PONDOK PESANTREN UBAY BIN KA'AB SALO - Rezky Saputra; Abel Renata, Ade Irma, Rena Revita (CV. ADIBA ASIHA AMIRA, 2024)
This research aims to examine the relationship between pedagogical competence and social competence of teachers at the Ubay bin Ka'ab Salo Islamic Boarding School. The method used in this research is interviews with sources and field observations to obtain comprehensive data. The research results show that good pedagogical competence, balanced with high social competence, contributes significantly to the formation of students' character and learning motivation. Apart from that, this research reveals that positive interactions between teachers and students can strengthen the learning process. It is hoped that the results of this research can provide valuable insights for the development of teacher professionalism in Islamic boarding school environments, as well as being a source of inspiration for further research in the field of education